De-escalation of radiotherapy for the treatment of HPV-associated head and neck cancer: A case report and a word of caution. Issue 1 (1st January 2017) - Keller, Andrew; Harvey, Mark E.; Kameh, Darian S.; Haughey, Bruce; Ho, Henry; Magnuson, Scott; Akhtar, Adnan; Mekhail, Tarek; Zehngebot, Lee; Rao, Nikhil G.
Abstract: Background: It has been noted that HPV associated head and neck cancers have an increased responsiveness to radiotherapy. For this reason, strategies at de-escalation are currently being prospectively evaluated. Methods: We report a case of a 58-year-old male who presented with a right neck mass and was diagnosed with HPV associated, p16 positive, cT2N2bM0 tonsillar squamous cell carcinoma. The patient unintentionally received reduced doses of radiation and systemic therapy due to inability to tolerate treatment. Results: The patient was found to have no evidence of disease on 4-month follow-up PET scan and clinical exam. However, several months later, he developed disease recurrence and ultimately required surgical salvage. Conclusions: Until mature results from prospective phase 3 clinical trials are available, we recommend caution in the de-intensification of therapy particularly as current therapy achieves high rates of long term disease control.